School infrastructure in the Philippines: Where are we now and where should we be heading? - Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2022)
This study assesses the adequacy of school infrastructure in the Philippine basic education sector and conducts benchmarking against developmental targets and other countries' performance. The study shows that with respect to classrooms, there had been progress in decongesting schools, but spatial inequality in classroom-student ratio exists and must be addressed. Spatial inequality is evident given the congested classrooms in some administrative regions. Moreover, additional classrooms are needed given that school buildings in certain remote areas do not meet quality and safety standards, enrolment is increasing, and existing classrooms deteriorate due to wear and tear and calamities. With respect to water, sanitation, and hygiene (WASH) facilities, the gaps are huge and become more visible when benchmarked against other countries. The Philippines is lagging behind most countries in the Eastern and South-Eastern Asia region in providing WASH facilities to schools, even when compared with neighboring countries that have lower per capita income. With respect to electricity access of schools, many countries in the Eastern and South-Eastern Asia region have already achieved universal access and yet the Philippines still struggles to complete the electrification of schools.
Keywords: 330; human capital; school infrastructure; school buildings; WASH facilities; electricity access; ICT access